2015
DOI: 10.1098/rspa.2014.0588
|View full text |Cite
|
Sign up to set email alerts
|

A new inverse regression model applied to radiation biodosimetry

Abstract: Biological dosimetry based on chromosome aberration scoring in peripheral blood lymphocytes enables timely assessment of the ionizing radiation dose absorbed by an individual. Here, new Bayesian-type count data inverse regression methods are introduced for situations where responses are Poisson or two-parameter compound Poisson distributed. Our Poisson models are calculated in a closed form, by means of Hermite and negative binomial (NB) distributions. For compound Poisson responses, complete and simplified mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…The MULTIBIODOSE simplification provides more conservative dose estimation uncertainties than the ISO method, due to the fact that the largest covariance of the calibration curve fitting is negative ( Table 1). The IAEA simplification is not always conservative, in contrast to the more detailed Merkle methodology which includes both scoring uncertainty and error on the curve coefficients (IAEA 2011;Higueras et al 2015), and thus which results in the largest uncertainties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MULTIBIODOSE simplification provides more conservative dose estimation uncertainties than the ISO method, due to the fact that the largest covariance of the calibration curve fitting is negative ( Table 1). The IAEA simplification is not always conservative, in contrast to the more detailed Merkle methodology which includes both scoring uncertainty and error on the curve coefficients (IAEA 2011;Higueras et al 2015), and thus which results in the largest uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications have demonstrated that distributions other than the Poisson may be more applicable to yields of chromosome aberrations (e.g. Ainsbury et al 2013;Higueras et al 2015, Oliveira et al 2016, for example, and thus it is possible that radiation dose estimates may be more accurately described by alternative distributions to the Poisson. The Bayesian approach allows much more accurate characterization of the dose distribution as it is based on the combined information regarding the potential dose and exposure scenario, the calibration coefficients and the yield of aberrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is currently growing acceptance of Bayesian methodologies, since they allow inclusion of previous information about the circumstances of exposure ( 7072 ). More user-friendly software platforms based on Bayesian modeling have been developed to estimate radiation exposures including CytobayesJ and radir, a cytogenetic biodosimetry dose estimation application tailored for use in the R software platform ( 73 , 74 ).…”
Section: Cytogeneticsmentioning
confidence: 99%
“…Numerous effects of radiation have been identified in association with mutations and genomic instability (breaks and actions in repair genes), angiogenesis (vascularisation and hypoxia), apoptosis (changes in p53), proliferative signaling (EGCR and TGF-α), suppression of cell cycle (ATM, p53 lock), energy dysregulation (HIF, c-MyC, glycolytic pathways inhibitors), tumor promotion and inflammation (p53 and ROS) and activation and inactivation of metastases (hypoxia, lactate) (Boss et al, 2014). Given the risks of cancer, studies suggest biological dosimeters guided by genetic instability mechanisms, is noted in summary in Table 3, especially for chromo-somal aberrations that may be markers for evaluation of dose and biological effects induced by IR (Higueras et al, 2015). Numerous effects of radiation (Table 3) have been identified in association with mutations and genomic instability (breaks and actions in repair genes), angiogenesis (vascularization and hypoxia), apoptosis (changes in p53), proliferative signaling (EGCR and TGF-α), suppression of cell cycle (ATM, locking p53), energy deregulation (HIF, c-MyC, glycolytic pathways inhibitors), tumor promotion and inflammation (p53 and ROS) and activation and inactivation of metastases (hypoxia, lactate) (Boss et al, 2014;Lee et al, 2014).…”
Section: Nuclear Changes Induced By Occupational Exposure To Ir In Ormentioning
confidence: 99%